PERLINDUNGAN HUKUM BAGI KORBAN KECELAKAAN LALU LINTAS DALAM ASURANSI SOSIAL PT. JASA RAHARJA - Zulfa Hadiaraya (2021)
Legal protection, is an effort of law enforcers to protect the rights of a person's interests, which are granted in accordance with applicable legal rules. A single accident is an event that occurs suddenly without being predicted or planned and is uncontrollable and only involves one motorized vehicle without involving other road users. A single accident that is excluded in the regulation regarding the acquisition of accident compensation fund rights, makes the public complain about this because there is no guarantee and legal protection for the victim who experiences it. Accidents are things that are never expected, whether they are accidents that occur due to external or internal factors. In this study, the authors wanted to examine why a single accident was not borne by PT. Jasa Raharja and legal protection for victims of a single accident. The method in this research uses normative juridical with statutory approach and case study methods. The conclusion of this paper is that a single accident does not exist in the types of accidents that can be borne by PT. Jasa Raharja, as well as victims who experience it, can get legal protection and guarantees provided by the Health Social Security Administering Body. Keywords : legal protection, PT. Jasa Raharja, a single accident.